The Role of The Sharia Supervisory Board In Sharia Banking In Indonesia - Mukhtar Adinugroho; Teguh Herlambang; Moh. Saiful Hakiki; Firman Yudianto (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
One of the characteristics that distinguishes Islamic Commercial Banks from conventional banks is the existence of a sharia supervisory board (DPS) at an independent Islamic bank and located parallel to the board of commissioners. DPS, has an important and strategic role in the implementation of sharia in Islamic Banks. DPS is responsible for ensuring that all products and procedures of Islamic Banks comply with sharia principles. This research is entirely a literature review. The purpose of this research is to find out about the role of DPS in Islamic banking. The analytical method used is content analysis method. The results of this study indicate that the DPS is an independent body consisting of muamalah sharia experts who also have knowledge in banking in Islamic financial institutions and are tasked with overseeing the implementation of the decisions of the national sharia board at these sharia financial institutions. DPS has an important and strategic role in the application of sharia principles in sharia banking. DPS is responsible for ensuring that all sharia bank products and procedures comply with sharia principles.